Best Answer

That will depend on the plus or minus value of 4y in order to simplify the given expression

Q: What is the answer of 9x 4y -6x - 5y?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

(6x - 5y) + (-3x - 4y) =6x - 5y - 3x - 4y =3x - 9y =3 (x - 3y)

5x-4y+9y+x-9+7 = 5x + x - 4y + 9y - 9 + 7 = 6x + 5y - 2 ■

5y

6x and 5y

(6x)(5y)

Related questions

(6x - 5y) + (-3x - 4y) =6x - 5y - 3x - 4y =3x - 9y =3 (x - 3y)

6x-3y

7.8.8

86

It can be simplified to: 9y-2x

-9x + 2y = -69 So 2y = 9x - 69 The other equation can be written as 6x - 4y = 54 or 6x - 2*2y = 54 Substituting for 2y gives 6x - 2*(9x - 69) = 54 6x - 18x + 138 = 54 12x = 84 x = 7 and then 2y = 9x - 69 = 9*7 - 69 = 63-69 = -6 so that y = -3

2p = 4y - 12xy - 6x, 3q = 12 - 15y so 2p - 3q = 4y - 12xy - 6x - (12 - 15y) = 4y - 12xy - 6x - 12 + 15y = 19y -12xy - 6x - 12

5x-4y+9y+x-9+7 = 5x + x - 4y + 9y - 9 + 7 = 6x + 5y - 2 ■

5y

x = 2, y = 3

5y - y = 4y

6x and 5y